2021
DOI: 10.1097/wad.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noninvasive Brain Stimulation (NIBS) on Cognitive Impairment in Mild Cognitive Impairment and Alzheimer Disease

Abstract: Objective: The purpose of this meta-analysis was to evaluate the beneficial effects and optimal stimulation protocol of noninvasive brain stimulation (NIBS) including repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) on patients with mild cognitive impairment and Alzheimer disease. Materials and Methods: PubMed, Web of Science, Embase, and the Cochrane Library were searched until March 2020. The cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…[114][115][116] In addition, the beneficial effect of tDCS treatment on cognitive performance has also been demonstrated in patients with mild cognitive impairment and Alzheimer's disease. 69,117 Furthermore, stimulation with tDCS in aging individuals improved performance on semantic word generation task, 111 naming, 118 associative learning task, 119 and delayed episodic memory tasks. [120][121][122]…”
Section: Cognitive and Memory Deficitsmentioning
confidence: 96%
See 2 more Smart Citations
“…[114][115][116] In addition, the beneficial effect of tDCS treatment on cognitive performance has also been demonstrated in patients with mild cognitive impairment and Alzheimer's disease. 69,117 Furthermore, stimulation with tDCS in aging individuals improved performance on semantic word generation task, 111 naming, 118 associative learning task, 119 and delayed episodic memory tasks. [120][121][122]…”
Section: Cognitive and Memory Deficitsmentioning
confidence: 96%
“…A systematic review found that eight of 12 studies using rTMS application over DLPFC in elderly people showed significant cognitive improvements, 65 and a meta‐analysis study concluded that rTMS has positive effect on cognitive improvement in healthy aging and Alzheimer's disease. 66 In addition, numerous meta‐analysis studies have shown that the application of rTMS produces precognitive effects in patients with mild cognitive impairment and Alzheimer's disease 67 , 68 , 69 , 70 and in patients with cognitive deficits and dementia. 71 , 72 , 73 The beneficial effect of rTMS treatment has also been shown in improving episodic memory in cognitively deficient individuals 74 and in reverting cognitive impairments in celiac disease patients.…”
Section: Noninvasive Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Anodal stimulation in MCI patients also shows improved performance on immediate verbal memory ( Fileccia et al, 2019 ). Several meta-analyses ( Wang et al, 2021 ; Majdi et al, 2022 ) have confirmed the efficacy of anodal stimulation on the DLPFC in MCI and AD patients on memory tests. However, a recent review ( Ciullo et al, 2021 ) reported that evidence of a positive effect on memory is inconclusive in AD and weak in MCI.…”
Section: Introductionmentioning
confidence: 96%
“…Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive neuromodulation technique which has been considered as a well-tolerated and adjustable technology without serious adverse effects 7 . It has been widely applied to improve cognitive impairment in MCI research in recent years.…”
mentioning
confidence: 99%